IMPLEMENTASI NILAI-NILAI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN 11 SP 4 PAOH KECAMATAN TEMPUNAK - Rahmat Rahmat; Ubabuddin Ubabuddin (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2022)
Educational institutions are considered as the most effective institutions in cultivating students' character values because they are considered capable of making a major contribution in limiting changes in situations from a moral crisis which can result in the decline of the good character of the nation's children. Given the importance of instilling character values in students from an early age, SDN 11 SP 4 Paoh tries to instill character values and implement them in everyday life. Good character can continue to develop and be realized with maximum effort, and is able to produce positive activities. The development of character values from an early age is absolutely necessary so that the values displayed when they grow up will be better and understand all the differences that exist. The results of the study show: 1. The values of character education that are integrated into learning are religious values, discipline, perseverance, curiosity, caring, and responsibility. 2. The implementation of character education values in extracurricular activities is through TPA, dance, sports and enrichment activities by providing motivation, understanding, role models, advice, sanctions and prizes